BEST PRACTICE OF ENTERPRISE RISK MANAGEMENT: THE IMPACT ON RURALS’ BANK PERFORMANCE - Candy, Candy (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to examine the role of enterprise risk management (ERM) on rural banks' performance. ERM is measured by the structure, governance, and process in the risk management process. The bank performance as the dependent variable use measurement both financial and non-financial. The study sample is the rural banks in Riau Island provinces, consisting of 63 questionnaires as the data for further analysis. The result showed that ERM enhances the rural banks' performance, both financial and non-financial. It showed that the practice of ERM does well when the rural bank is well-established.